Vegetative Propagation through Branch Cuttings in Dalbergia sissoo Roxb. - Gupta, B. B.; Kumar, Adarsh; Negi, D. S. (Indian Forester, 1993)
Studies on the rooting response of stem cuttings of Dalbergia sissoo in relation to the Season, age of the mother tree, position of cuttings on shoot axis and treatment with auxins, IBA, IAA and NAA and mixture of NAA + IBA. The study revealed that cuttings taken from 4 years old plants rooted better when planted in the month of August in comparison to other months. A substantial increase in the percentage of rooting occurred when treated with IBA 100 ppm in the month of August. The cuttings from younger plants rooted readily and rooting percentage fell appreciably in case of cuttings from old tree.